2022
DOI: 10.1108/hff-11-2021-0722
|View full text |Cite
|
Sign up to set email alerts
|

How do artificial bacteria behave in magnetized nanofluid with variable thermal conductivity: application of tumor reduction and cancer cells destruction

Abstract: Purpose The study aims to determine an efficiency of external magnetic field on the bacteria surrounded by thousands of magnetic magnetite nanoparticles. The interstitial nanoliquid in which an artificial bacteria swims in biological cell is utilized with variable thermal conductivity. Two dimensions unsteady motion of second grade fluid are considered. The stretching wall is taken as a curved surface pattern. Design/methodology/approach The mathematical results have been obtained by Chebyshev pseudospectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…We observed excellent agreement between the results for all profiles. Table 3 shows a comparison between the current and previous results (Elgazery et al, 2022) for skin friction and it was found that both results agreed. Figures 2A-D show comparison between HAM and numerical solutions for the temperature θ(ξ), pressure p(ξ), velocity f ′(ξ), the bacterial density field χ(ξ), nutrient concentration ω(ξ).…”
Section: Validations Of the Resultsmentioning
confidence: 58%
“…We observed excellent agreement between the results for all profiles. Table 3 shows a comparison between the current and previous results (Elgazery et al, 2022) for skin friction and it was found that both results agreed. Figures 2A-D show comparison between HAM and numerical solutions for the temperature θ(ξ), pressure p(ξ), velocity f ′(ξ), the bacterial density field χ(ξ), nutrient concentration ω(ξ).…”
Section: Validations Of the Resultsmentioning
confidence: 58%
“…subject to the boundary condition (Elgazery et al, 2022) u U w as 1 − ct , v 0, T T w , ρ n ρ n w , n n w at r → 0…”
Section: Governing Equations and Boundary Conditions After Applying A...mentioning
confidence: 99%
“… Anantha Kumar et al (2020b) examined the Casson fluid issue in the context of heat radiation-influenced exponentially stretched curved surfaces. Other simulations and investigations of entropy analyses with applications may be seen in Ghachem et al (2018), Elgazery et al (2022) , Rooman et al (2022) , and Maatki (2023) .…”
Section: Introductionmentioning
confidence: 99%